Cycle-slip Detection Method Considering Clock Jump for GNSS Raw Observation of Smartphones. Issue 1 (1st February 2022) - Liu, Xing; Li, Chunhua; Li, Cailing; Gao, Pan
Abstract: Using low-cost sensors to achieve high-precision positioning has been a hot research topic in autonomous driving technology, and smartphones not only have the advantages of low cost and easy installation, but also can provide high-precision navigation and positioning services. In this paper, we focus on the cycle-slip detection method based on the original Global Navigation Satellite System (GNSS) observations of smartphones. In response to the problem that the phase value of smartphone GNSS has serious cycle slip and the existence of frequent clock jumps will affect the cycle slip detection, a cycle slip detection method that integrates clock jumps and single and dual frequency observations is proposed. The experiments show that the method can effectively detect the continuous and as small as 0.5 week of cycle slip for the phase observations with the sampling rate of 1 Hz. The root mean square error (RMSE) in the L1 and L5 phase residuals after the cycle slip repair is 7.0 mm and 8.3 mm, respectively, with an accuracy improvement of 18.16% and 9.62%, which indicates that this method is effective and feasible.